EKSIL POLITIK DALAM PERSPEKTIF HUKUM PENGUNGSI INTERNASIONAL - Muhammad Faisal; Siti Muslimah; Ayub Torry Satrio Kusumo (Faculty of Law Universitas Sebelas Maret, 2017)
This research discusses the experience of Indonesian exiles. Presented in a chronological order from their departure to foreign countries until the post-Suharto era. It shows a strong interaction between international and domestic political battles as the context of their origin. Organized based on observations of the Indonesian exiles, in addition to related literature review, this research points out the effort by the exiles to maintain their nasionalist commitment by creating a counter narrative to Indonesian historiography that neglected them. This research is normative legal research which is descriptive. In nature the data used in this research is secondary data including primary legal materials, secondary and tertiary. Data collection techniques used is library study and through cyber media. A Convention 1951 on the status of refugees and the 1967 Additional Protocol will be the main instrument to be considered. Technical analysis is content analysis method.The results showed that the presence of exiles in accordance with the definition of a refugee under the Vienna Convention 1951 and Protocol of 1967. In addition, as a result of government policy in the past makes the fulfillment of the political-constitutional rights as citizens exile has not fulfilled properly according to the UUD 1945.